Growth kinetics and fitness of fluoroquinolone resistant and susceptible Campylobacter jejuni strains of cattle origin - Goulart, Debora Brito; Zhang, Qijing; Sahin, Orhan (Frontiers in Veterinary Science, 2023)
Human enterocolitis is frequently caused by the Gram-negative microaerobic bacterium Campylobacter jejuni. Macrolides (e.g., erythromycin) and fluoroquinolones (FQs) (e.g., ciprofloxacin) are the preferred antibiotics for the treatment of human campylobacteriosis. Rapid emergence of FQ-resistant (FQ-R) Campylobacter during treatment with FQ antimicrobials is well known to occur in poultry. Cattle is also an important reservoir of Campylobacter for humans, and FQ-R Campylobacter from cattle has become highly prevalent in recent years. Even though the selection pressure may have contributed to the expansion of FQ-R Campylobacter, the actual impact of this factor appears to be rather low. In this study, we examined the hypothesis that the fitness of FQ-R Campylobacter may have also played a role in the rise seen in FQ-R Campylobacter isolates by employing a series of in vitro experiments in MH broth and bovine fecal extract. First, it was shown that FQ-R and FQ-susceptible (FQ-S) C. jejuni strains of cattle origin had comparable growth rates when individually cultured in both MH broth and the fecal extract with no antibiotic present. Interestingly, FQ-R strains had small but statistically significant increases over FQ-S strains in growth in competition experiments performed in mixed cultures with no antibiotic present. Lastly, it was observed that FQ-S C. jejuni strains developed resistance to ciprofloxacin more readily at high initial bacterial cell density (107 CFU/mL) and when exposed to low levels of the antibiotic (2–4 μg/mL) compared with that at a low level of initial bacterial cell density (105 CFU/mL) and exposure to a high level of ciprofloxacin (20 μg/mL) in both MH broth and the fecal extract. Altogether, these findings indicate that even though FQ-R C. jejuni of cattle origin may have a slightly higher fitness advantage over the FQ-S population, the emergence of FQ-R mutants from susceptible strains is primarily dictated by the bacterial cell density and the antibiotic concentration exposed under in vitro condition. These observation may also provide plausible explanations for the high prevalence of FQ-R C. jejuni in cattle production due to its overall fit nature in the absence of antibiotic selection pressure and for the paucity of development of FQ-R C. jejuni in the cattle intestine in response to FQ-treatment, as observed in our recent studies.